2020
DOI: 10.1002/adma.202002736
|View full text |Cite
|
Sign up to set email alerts
|

Metal Halide Perovskite Nanorods: Shape Matters

Abstract: have a soft and ionic lattice. [3] Such ionic nature makes it possible to conduct anion exchange reactions from one kind of perovskite NCs, for example CsPbBr 3 , to another and thus achieve particles with different compositions such as CsPbCl 3 , CsPbI 3 , and their mixed-anion alloys, which is changing to accomplish for conventional semiconductor NCs. This enables bandgap tuning over the whole visible and even near-infrared spectral ranges while maintaining the size and morphology of the resulting NCs. [4] H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 150 publications
0
50
0
Order By: Relevance
“…[ 1–5 ] CsPbX 3 QDs exhibit excellent optical properties such as high photoluminescence quantum yields (PLQYs), narrow full width at half‐maximum (FWHM), and tunable bandgaps, which is comparable or even superior to state‐of‐the‐art CdSe QDs with sophisticated shelling or surface passivation, showing huge potential for lighting/display applications. [ 1,2,5–11 ] Recently, it was demonstrated that CsPbI 3 QDs can keep a stable black phase at room temperature, [ 12 ] whereas bulk CsPbI 3 will convert to a nonperovskite yellow phase ( δ ‐phase) with unfavorable optoelectronic properties at the temperature below 320 °C. In addition to the extraordinary phase stability, CsPbI 3 QDs also possess superior thermal stability over the widely studied organic–inorganic hybrid perovskites.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–5 ] CsPbX 3 QDs exhibit excellent optical properties such as high photoluminescence quantum yields (PLQYs), narrow full width at half‐maximum (FWHM), and tunable bandgaps, which is comparable or even superior to state‐of‐the‐art CdSe QDs with sophisticated shelling or surface passivation, showing huge potential for lighting/display applications. [ 1,2,5–11 ] Recently, it was demonstrated that CsPbI 3 QDs can keep a stable black phase at room temperature, [ 12 ] whereas bulk CsPbI 3 will convert to a nonperovskite yellow phase ( δ ‐phase) with unfavorable optoelectronic properties at the temperature below 320 °C. In addition to the extraordinary phase stability, CsPbI 3 QDs also possess superior thermal stability over the widely studied organic–inorganic hybrid perovskites.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, halide perovskite nanocrystals (NCs) have attracted significant attention in both fundamental research and industrial applications, owing to their excellent optical and electronic properties including tunable emission across the UV–vis spectral range, high extinction coefficient, narrow luminescence line width, high photoluminescence quantum yield (PLQY), and high defect tolerance. [ 1–4 ] These intrinsic properties make them promising candidates for a wide range of applications, such as light‐emitting diodes (LEDs), [ 5–7 ] lasers, [ 8,9 ] photodetectors, [ 10 ] biological probes, [ 11 ] solar cells, [ 12 ] and photocatalysis. [ 13 ] In particular, their remarkable optoelectronic performances render them a possible game‐changer.…”
Section: Introductionmentioning
confidence: 99%
“…luminescence line width, high photoluminescence quantum yield (PLQY), and high defect tolerance. [1][2][3][4] These intrinsic properties make them promising candidates for a wide range of applications, such as light-emitting diodes (LEDs), [5][6][7] lasers, [8,9] photodetectors, [10] biological probes, [11] solar cells, [12] and photocatalysis. [13] In particular, their remarkable optoelectronic performances render them a possible game-changer.…”
mentioning
confidence: 99%
“…2,3,4 Lead-halide perovskite NCs combine high photoluminescence quantum yields (PLQYs) with narrow emission profiles and tunable fluorescence related to the halide composition 5 or to morphology. 6 On the other hand, although lead-halide perovskite NCs can tolerate a relatively large concentration of defects without compromising their semiconducting properties, 7 the achievement of near-unity PLQYs is severely undermined by halide vacancies 8 prevalently placed at their surface. 9,10,11 In order to cope with this issue, it has recently been proposed, in the course of the synthesis, to separately combine the precursors of the three elements (cesium, lead and the halides) composing the CsPbX 3 NCs, thus allowing to establish the proper halide-rich synthetic conditions, 12 difficultly attainable by using the common approach based on the use of PbX 2 salts as both lead and halide source.…”
Section: Introductionmentioning
confidence: 99%